IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 14/PUU-XI/2013 TENTANG PEMILIHAN UMUM SECARA SERENTAK - Ashari ,SH (Fakultas Hukum Universitas Mataram, 2016)
Implications of Constitutional Court Decision No. 14 / PUU-XI / 2013 on General Election In Unison. Law No. 8 Year 2011 concerning the Constitutional Court in Article 47 states that the Constitutional Court's decision had permanent legal power since completed pronounced a plenary session open to the public, so that the provisions of article that declared contrary to the 1945 Constitution as positive since the Constitutional Court decision was read, missing positive qualities as legal and can not be used as a basis for legitimate legal action. However, in order to enforce the law and justice for the people as holders of constitutional rights, the Constitutional Court is required to make breakthroughs law to be able to arrive in the idea that sometimes can not be reached by applicable law, as well as legal consequences in delaying the decision.Keywords: Constitutional Court, Effects,Simultaneous Election